Dialektika Komunikasi pada Debat Pilpres 2019 dalam Perspektif Al-Qur’an - Wahab Nur Kadri (Dakwah Institut PTIQ Jakarta, 2020)
The 2019 Presidential Debate contained in the Qur'an about the Jadal verses through the Dialectic Communication perspective also by studying more deeply and philosophically. This discussion leads the author to discuss the science of communication and the Qur'an with stories and history in a special discussion: about the schedule that arises due to the